2019
DOI: 10.3390/ijerph16162902
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Fuzzy AHP and Fuzzy TOPSIS Approach to Assess Sustainable Urban Development in an Emerging Economy

Abstract: Sustainable urban development (SUD) requires a balance between economic growth, social well-being, and environmental protection. Oftentimes, urban policy makers can hardly fulfill all SUD goals due to inadequacy of resources to support SUD programs. Therefore, the process of allocating scarce resources to achieve and balance various SUD goals becomes a critical challenge for policy makers and researchers. To solve this problem, this study adopts fuzzy Analytic Hierarchy Process (AHP) and fuzzy Technique for Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…Because FAHP considers the uncertainty of a problem, multiple criteria, and experts' opinions, especially in cases where numerous decision criteria and alternatives are available, it can avoid an overly subjective pairwise comparison value and provide a more precise result. Dang et al [32] adopted it to evaluate several cities in an emerging economy (Vietnam). In the present study, FAHP was used as the research method.…”
Section: Methodsmentioning
confidence: 99%
“…Because FAHP considers the uncertainty of a problem, multiple criteria, and experts' opinions, especially in cases where numerous decision criteria and alternatives are available, it can avoid an overly subjective pairwise comparison value and provide a more precise result. Dang et al [32] adopted it to evaluate several cities in an emerging economy (Vietnam). In the present study, FAHP was used as the research method.…”
Section: Methodsmentioning
confidence: 99%
“…Government barriers include lack of subsidies and funds, less interest of the government, lack of promotional activities by the government, lack of legislation by government, and lack of government intervention regarding the research and development activities in educational institutes. [ 14,24–26 ] Qian and Chan [ 27 ] elaborated that government lacks suitable implementation of legislation to control the energy‐saving rules and regulations regarding the adoption of SETs in the construction industry. Mardani, Zavadskas, Streimikiene, Jusoh, Nor and Khoshnoudi [ 1 ] analyzed that the government was not interested in providing funds for stakeholders to adopt and promote the SETs in construction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 1 ] Alam [ 13 ] Identified that loan schemes on with less interest rates and lack of awareness of SETs adoptions are important barriers that hinder the adoption of SETs in construction projects. Dang, Wang and Dang [ 14 ] found that lack of building energy codes related to energy management in buildings and lack of professionals’ skills and experience are significant barriers that slow down the adoption of SETs in construction projects. Less interest from the top leadership in the development of SETs and lack of improper use of SETs are also important issues that create hurdles to adopt SETs in construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars at home and abroad have conducted various studies on the interactions between economic development and ecology. Research has shown that only through economic and ecological principles, with trends of synergy, interaction, and simultaneous development [3], will sustainable development be achieved [4,5].…”
Section: Introductionmentioning
confidence: 99%